Panchakarma Excerpts From Chikitsa Sangraha : A Book Review - Amrithalatha , K; Jigeesh , P P (International Research Journal of Ayurveda & Yoga, 2022)
Historically, Panchakarma had a pivotal role in treating patients of Kerala through the contributions of ancient physicians and their role in reforming Panchakarma to its current form is invaluable. Most of them couldn’t document their experiences as the social context was unfavourable at that time and the methods of treatment varied in different localities. There were scarcely any undertakings for giving them a unified form. Chikitsa sangraham is one of the few works that documented the treatment methods of that era and led to the consolidation of at least some of the regional changes in practicing the Panchakarma procedures. A summary of the Panchakarma given below was based on the handbook by the eminent P.S Warrier, who developed his own changes based on convenience and practicality. Chikitsa sangraham is an introductory book on Ayurveda that was published with the aim of creating general awareness about Ayurveda among a group of people ranging from ordinary people to